Trained Innate Immunity by Repeated Low-Dose Lipopolysaccharide Injections Displays Long-Term Neuroprotective Effects - Xiao-yan Zhou; Rong Gao; Jian Hu; Da-peng Gao; Yan-ling Liao; Jian-jun Yang (Mediators of Inflammation)
Disrupted immune response is an important feature of many neurodegenerative conditions, including sepsis-associated cognitive impairment. Accumulating evidence has demonstrated that immune memory occurs in microglia, which has a significant impact on pathological hallmarks of neurological diseases. However, it remains unclear whether immune memory can cause subsequent alterations in the brain immune response and affect neurobehavioral outcomes in sepsis survivors. In the present study, mice received daily intraperitoneal injection of low-dose lipopolysaccharide (LPS, 0.1 mg/kg) for three consecutive days to induce immune memory (immune tolerance) and then were subjected to sham operation or cecal ligation and puncture (CLP) 9 months later, followed by a battery of neurobehavioral and biochemical studies. Here, we showed that repeated low-dose LPS injection-induced immune memory protected mice from sepsis-induced cognitive and affective impairments, which were accompanied by significantly decreased brain proinflammatory cytokines and immune response. In conclusion, our study suggests that modulation of brain immune responses by repeated LPS injections confers neuroprotective effects by preventing overactivated immune response in response to subsequent septic insult.